Applications of digital PCR in COVID‐19 pandemic. Issue 2 (1st January 2021) - Tan, Chianru; Fan, Dongdong; Wang, Nan; Wang, Fang; Wang, Bo; Zhu, Lingxiang; Guo, Yong
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has led to a public health crisis and global panic. This infectious disease is caused by a novel coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Digital polymerase chain reaction (dPCR), which is an emerging nucleic acid amplification technology that allows absolute quantification of nucleic acids, plays an important role in the detection of SARS‐CoV‐2. In this review, we introduce the principle and advantages of dPCR, and review the applications of dPCR in the COVID‐19 pandemic, including detection of low copy number viruses, measurement of the viral load, preparation of reference materials, monitoring of virus concentration in the environment, detection of viral mutations, and evaluation of anti‐SARS‐CoV‐2 drugs. We also discuss the challenges of dPCR in clinical practice. Abstract : The coronavirus disease 2019 (COVID‐19) pandemic has led to a public health crisis and global panic. Digital polymerase chain reaction (dPCR), which is an emerging nucleic acid amplification technology that allows absolute quantification of nucleic acids, plays an important role in the detection of the pathogen of COVID‐19. In this review, the authors introduce the principle and advantages of dPCR, review the applications of dPCR in the COVID‐19 pandemic, and discuss the challenges of dPCR in clinical practice.